East African agriculture and climate change: A comprehensive analysis - Burundi - Baramburiye, Juvent; Kyotalimye, Miriam; Thomas, Timothy S.; Waithaka, Michael (International Food Policy Research Institute, 2012)
Burundi is a small, landlocked country of which only 36 percent is arable. The malnutrition rate for children under five years is high; thirty-nine out of every 100 children weigh less than is normal for their age. Burundi’s population of 8 million is young and growing rapidly: Nearly 7 out 10 Burundians are under the age of 15, and the annual growth rate is 2.8 percent.